2013
DOI: 10.1371/journal.pone.0082939
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Dispositional Optimism and Psychological Resilience on the Subjective Well-Being of Burn Patients: A Structural Equation Modelling Analysis

Abstract: Burn wounds are severely stressful events that can have a significant impact on the mental health of patients. However, the impact of burns on individuals with different personality traits can be different. The present study aimed to investigate the impact of dispositional optimism on the subjective well-being of burn patients, and mainly focused on the confirmation of the mediator role of psychological resilience. 410 burn patients from five general hospitals in Xi'an accomplished the revised Life Orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 50 publications
8
91
0
7
Order By: Relevance
“…23 The quality of relationships identified by study participants was found to vary from "hurtful and difficult" through to "helpful and uplifting" 10 and either empowering or disempowering. 18 In contrast to the majority of included papers however, Yang et al 20 found no significant correlation with social support and resilience; social support was instead correlated with optimism.…”
Section: Relational Strengthsmentioning
confidence: 92%
See 4 more Smart Citations
“…23 The quality of relationships identified by study participants was found to vary from "hurtful and difficult" through to "helpful and uplifting" 10 and either empowering or disempowering. 18 In contrast to the majority of included papers however, Yang et al 20 found no significant correlation with social support and resilience; social support was instead correlated with optimism.…”
Section: Relational Strengthsmentioning
confidence: 92%
“…Positive coping was significantly related to overall resilience and with each of the resilience dimensions of tenacity, strength, and optimism. He et al 18 also found that dispositional optimism, defined as the capacity to recover from frustration, directly and significantly increased subjective well-being in adult burn survivors. Furthermore, optimism was mediated by resilience to impact on subjective well-being.…”
Section: Positive Copingmentioning
confidence: 95%
See 3 more Smart Citations